Kontribusi Komunikasi Interpersonal dan Iklim Kerja Terhadap Motivasi Kerja Guru SMA Negeri di Kecamatan Rambah dan Rambah Hilir Kabupaten Rokan Hulu Provinsi Riau - -, Hardianto (Universitas Pasir Pengaraian, 2012)
Based of afield observation, it indicated that the workmotivation teachers of the senior high school in sub districtRambah and Rambah Hilir Rokan Hulu Regency Riau Provinceis not optimal. Researcher suspected the interpersonalcommunication and work climate affects teachers workmotivation Senior High Schools in sub district Rambah andRambah Hilir Rokan Hulu Regency Riau Province, thereforeresearch must be done to test its truth.This research aimed to reveal the contribution ofinterpersonal communication and work climate toward teacherswork motivation senior high schools in sub District Rambahand Rambah Hilir Rokan Hulu Regency Riau Province. Thehypothesis tested in this study were: 1) interpersonalcommunication to contribute to teachers work motivation, 2)work climate to contribute to teachers work motivation, 3)interpersonal communication and work climate jointlycontribute to teachers work motivation.Research population were all teachers of senior highschools at Sub District Rambah and Rambah Hilir Rokan HuluRegency Riau Province totaling 124 teachers from whom 59teachers were selected as research sample by using stratifiedproportional random sampling technique.